RHOB influences lung adenocarcinoma metastasis and resistance in a host‐sensitive manner1. Issue 2 (12th November 2013) - Luis-Ravelo, Diego; Antón, Iker; Zandueta, Carolina; Valencia, Karmele; Pajares, María-José; Agorreta, Jackeline; Montuenga, Luis; Vicent, Silvestre; Wistuba, Ignacio I.; De Las Rivas, Javier; Lecanda, Fernando
Abstract : Lung adenocarcinoma (ADC) is the most common lung cancer subtype and presents a high mortality rate. Clinical recurrence is often associated with the emergence of metastasis and treatment resistance. The purpose of this study was to identify genes with high prometastatic activity which could potentially account for treatment resistance. Global transcriptomic profiling was performed by robust microarray analysis in highly metastatic subpopulations. Extensive in vitro and in vivo functional studies were achieved by overexpression and by silencing gene expression. We identified the small GTPase RHOB as a gene that promotes early and late stages of metastasis in ADC. Gene silencing of RHOB prevented metastatic activity in a systemic murine model of bone metastasis. These effects were highly dependent on tumor‐host interactions. Clinical analysis revealed a marked association between high RHOB levels and poor survival. Consistently, high RHOB levels promote metastasis progression, taxane‐chemoresistance, and contribute to the survival advantage to γ‐irradiation. We postulate that RHOB belongs to a novel class of "genes of recurrence" that have a dual role in metastasis and treatment resistance. Highlights: RHOB is a novel prometastatic target in ADC. RHOB promotes treatment resistance. RHOB levels associate with clinical outcome.